1997
DOI: 10.1046/j.1365-3016.11.s1.8.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of interpregnancy interval to infant birthweight and length of gestation among low‐risk women, Georgia

Abstract: Summary. To examine the association between interpregnancy interval and low birthweight (5 2500 g), preterm delivery (5 37 weeks' gestation), and inadequate fetal growth, we studied a population-based sample of 23 388 white and 4885 black women at low risk for adverse pregnancy outcomes who delivered their first and second infants in Georgia from 1980 to 1992. We used fetal death and livebirth certificates. The interpregnancy interval was the time from delivery to the woman's next conception. For each pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 9 publications
0
41
1
2
Order By: Relevance
“…Although these differences might have introduced a bias in the observed associations, this would have been the case only if the association of first-born status with adult increased adiposity had been different between subjects who were followed up and those who were not. The median birth weight for gestational age of this sample was lower than that in the more recent African American reference population (38). This difference could be explained by secular trends or other differences between the 2 samples.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Although these differences might have introduced a bias in the observed associations, this would have been the case only if the association of first-born status with adult increased adiposity had been different between subjects who were followed up and those who were not. The median birth weight for gestational age of this sample was lower than that in the more recent African American reference population (38). This difference could be explained by secular trends or other differences between the 2 samples.…”
Section: Discussioncontrasting
confidence: 66%
“…Birth weight for gestational age was expressed as a z score based on a sex-and race-specific reference population (32,38).…”
Section: Discussionmentioning
confidence: 99%
“…In general, there were no significant differences in estimates of summary adjusted ORs between white and black women in subgroups that evaluated the effects of interpregnancy interval on adverse perinatal outcomes according to race/ethnicity. 39,40,52 For each month that interpregnancy interval was shortened from 18 months, the risk increase for preterm birth, LBW, and SGA was 1.9%, 3.3%, and 1.5%, respectively (TABLE 5). On the other hand, the risk for the 3 adverse perinatal outcomes increased by 0.6%, 0.9%, and 0.8%, respectively, for each month that interpregnancy interval was lengthened from 59 months.…”
Section: Birth Spacing and Risk Of Adverse Perinatal Outcomesmentioning
confidence: 99%
“…Most studies have found that a short interpregnancy interval was associated with increased risk for various adverse birth outcomes [7][8][9][10][11][12][13]. However, a review of the literature revealed a number of methodological limitations in previously published literature.…”
Section: Introductionmentioning
confidence: 99%